Pengaruh Kepemimpinan dan Budaya Sekolah terhadap Motivasi serta Dampaknya pada Kinerja Guru SMP Negeri di Kecamatan Juli Kabupaten Bireuen - Redha Marta, Muhammad; Iba, Zainuddin (Aceh Cooperative Care, 2024)
This teacher performance research examines the magnitude of the important contribution of leadership factors, school culture and motivation as intermediary factors. The case was conducted at a Public Junior High School in Juli District, Bireuen Regency, with a sample of 62 teachers. Using an associative method with a quantitative approach using path analysis. The results found the following: 1) there is a strong causal relationship between leadership and school culture and has a significant influence on motivation and has implications for teacher performance. 2). The leadership factor has a direct and indirect influence on motivation of 24.06% and on performance of 28.62%. 3) The school culture factor has a direct and indirect influence on motivation of 26.52% and on performance of 30.36%. 4) Simultaneously, leadership and school culture contribute to teacher performance, which is 17.25%.